An Experimental Contribution To The Kinetics Of Cementation - H. Barth; W. Gans; O. Knacke (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1973)
The rate of cementation was determined by measuring the time required to consume a thin electrodeposited layer of the cementating metal as indicated by a sudden increase in the electrical potential. The diffusion controlled cathodic current of the more positive metal was measured by conventional electrochemical techniques and compared with the cementation rate under the same experimental conditions. Micrographs revealed different types of crystal growth in different surroundings e.g. dendritic growth in acidic solutions.